Angiolymphoid hyperplasia with eosinophilia - Ghosh SK; Roy AK (Indian Journal of Dermatology, 1996)
ABSTRACT: A 28 year old female presented with multiple, firm, nodular lesions on the back of left pinna and adjoining skull with severe itching and eczematous changes of left pinna. Histopathology revealed picture consistent with angiolymphoid hyperplasia. The nodules persisted for 3 year and surgically excised.